Surgical management after perforation of Schneider's membrane during sinus lift: case report (Research, Society and Development, 2020)
Treatment with dental implants has been used to rehabilitate toothless patients through the fixed prosthesis on implants. In the maxilla, the alveolar bone may be compromised by bone resorption and pneumatization of the maxillary sinus, resulting in insufficient bone height for the implant installation. Thus, the lifting of the maxillary sinus (sinus lift) is a technique that allows the gain of bone volume in the posterior region of the maxilla, enabling rehabilitation with implants. This study aims to highlight a case where Schneider's membrane was perforated during a sinus lift and resolved during the operation. A 63-year-old male patient sought dental care complaining about his removable dental prostheses and longing to replace them with fixed prostheses on implants. On clinical and imaging examination, pneumatization of the maxillary sinus and insufficient bone height were found to install implants in the posterior region of the maxilla. The patient underwent a right maxillary sinus lift and during the procedure there was a 6mm perforation of the Schneidarian Membrane. This complication was solved by suturing the membrane to a perforation in the lateral bone wall of the maxillary sinus, which allowed the procedure to continue and be successful. It is concluded that the perforation of the Schneider membrane during the sinus lift procedure is a common trans-surgical complication and depending on the size of the perforation, there is a more appropriate approach to be performed. The technique chosen by the professional should be based on his clinical experience and scientific evidence.